Preparation of half- and post-metallocene hafnium complexes with tetrahydroquinoline and tetrahydrophenanthroline frameworks for olefin polymerization - Baek, Jun Won; Kwon, Su Jin; Lee, Hyun Ju; Kim, Tae Jin; Ryu, Ji Yeon; Lee, Junseong; Shin, Eun Ji; Lee, Ki Soo; Lee, Bun Yeoul (Polymers, 2019)
Hafnium complexes have drawn attention for their application as post-metallocene catalysts with unique performance in olefin polymerization. In this work, a series of half-metallocene HfMe2 complexes, bearing a tetrahydroquinoline framework, as well as a series of [Namido,N,Caryl]HfMe2-type post-metallocene complexes, bearing a tetrahydrophenanthroline framework, were prepared; the structures of the prepared Hf complexes were unambiguously confirmed by X-ray crystallography. When the prepared complexes were reacted with anhydrous [(C18H37)2N(H)Me]+[B(C6F5)4]-, desired ion-pair complexes, in which (C18H37)2NMe coordinated to the Hf center, were cleanly afforded. The activated complexes generated from the half-metallocene complexes were inactive for the copolymerization of ethylene/propylene, while those generated from post-metallocene complexes were active. Complex bearing bulky isopropyl substituents (12) exhibited the highest activity. However, the activity was approximately half that of the prototype pyridylamido-Hf Dow catalyst. The comonomer incorporation capability was also inferior to that of the pyridylamido-Hf Dow catalyst. However, 12 performed well in the coordinative chain transfer polymerization performed in the presence of (octyl)2Zn, converting all the fed (octyl)2Zn to (polyolefinyl)2Zn with controlled lengths of the polyolefinyl chain.
Keywords: Chain transfer polymerization; Comonomer incorporation; Hafnium complexes; Metallocene complexes; Olefin polymerization; Post-metallocene; Post-metallocene catalysts; Tetrahydroquinoline; Coordinative chain transfer polymerization; Hafnium complex; Half-metallocene; Olefin polymerization; Post-metallocene